Implementation of Smart Metering Systems: Challenges and Solutions - Hossein Shahinzadeh; Ayla Hasanalizadeh-Khosroshahi (Institute of Advanced Engineering and Science, 2014)
In recent decade, with advancements in telecommunications and information management systems technology and the increasing requirements of various sectors of the power industry for monitoring and controlling all of the network components (from production to consumption) power companies feel necessary to add intelligence to their grid as a scientific and practical solution to the utility industry. In most of the developed countries, electric power companies are planning to put priority on Smart Grid planning and for fulfilling this, implementation of Smart Metering Systems and energy management are the first and most basic step. Certainly, in the implementation of smart grids and smart metering infrastructure, power companies will face two major challenges, the cost of implementing these systems and the implementation complexity of the system. Therefore, this paper examines the challenges and strategies in order to better implementation of these systems in electrical grids.